Comparative Study of Thyroid Hormone Levels in Diabetic and Non Diabetic Patients of Bastar Region - Khan, Farah Aziz; Patil, S.K.B.; Khan, Mohammad Fareed; Nigam, Prashant (Asian Journal of Biological and Life Sciences, 2013)
Thyroid disorders and diabetes mellitus are the two most common endocrinopathies that frequently coexist. Unrecognized thyroid dysfunction may impair metabolic control in diabetic patients. Total of 120 subjects: 13 male and 107 female were studied. Subjects were classified into six major groups; diabetes only, hypothyroid only, hypothyroid with diabetes, hyperthyroid only, hyperthyroid with diabetes and control group. The data were statistically analyzed by ANOVA(analysis of variance) and Tukey's honest test to find difference at 0.05 level of significance respectively. Mean ± SD values of fasting sugar were increased in diabetes, hypothyroid with diabetes and hyperthyroid with diabetes without a significant difference between them. TSH mean values were increased in hypothyroid and hypothyroid with diabetes; and decreased in hyperthyroid and hyperthyroid with diabetes. No significant difference was observed between these groups. Mean values of T4 and FT4 were increased in hyperthyroid and hyperthyroid with diabetes, and also significantly differ from diabetes, hypothyroid, hypothyroid with diabetes. FT3 remain non-significant among all groups. We observed subclinical hypothyroidism, hyperthyroidism in old age females of type 2 diabetes mellitus (T2DM). The increased frequency of thyroid dysfunction in diabetic patients and its likely deleterious effects on metabolic function calls for a systematic approach to thyroid disease screening in diabetes.